2021
DOI: 10.3390/children8070583
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Differential Effects of School-Based Sitting and Movement Meditation on Creativity and Spatial Cognition: A Pilot Study

Abstract: Psychophysical well-being can be supported during development by the integration of extra-curricular activities in scholastic settings. These activities can be implemented in different forms, ranging from physical activities to sitting meditation practices. Considering that both such activities are thought to affect children’s psychophysical development, a movement-based meditation that combines the two approaches−in the form of a short daily activity−could represent a powerful tool to promote healthy physical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 98 publications
0
14
0
Order By: Relevance
“…cases removed 9 1115 6 7 0.38 0.02 − 0.02 to 0.11 0.45 1–10 0.0% 0.0% 0.0 to 64.8% 3.9 Creativity 345 5 14 0.05 0.01 − 0.16 to 0.18 0.92 1–11 83.2% 1.1% 0.0 to 84.7% 34.6 Infl. cases removed 10 315 5 13 − 0.31 − 0.05 − 0.22 to 0.13 0.55 1–11 84.8% 0.0% 0.0 to 84.8% 26.3 Significant associations are highlighted in bold; k = number of studies; I 2 at study level (level 3: between-study heterogeneity, level 2: within-study heterogeneity); β was estimated based on multiplying B by the SD of creativity and diving by the SD of effect size on the outcome; removed as influential studies: 1 85 , 86 ; 2 85 ; 3 87 ; 4 10 ; 5 88 ; 6 89 ; 7 90 ; 8 91 ; 9 92 , 93 ; 10 94 .
Figure 3 Estimate of the association between effect size and creativity rating of the physical activity interventions.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…cases removed 9 1115 6 7 0.38 0.02 − 0.02 to 0.11 0.45 1–10 0.0% 0.0% 0.0 to 64.8% 3.9 Creativity 345 5 14 0.05 0.01 − 0.16 to 0.18 0.92 1–11 83.2% 1.1% 0.0 to 84.7% 34.6 Infl. cases removed 10 315 5 13 − 0.31 − 0.05 − 0.22 to 0.13 0.55 1–11 84.8% 0.0% 0.0 to 84.8% 26.3 Significant associations are highlighted in bold; k = number of studies; I 2 at study level (level 3: between-study heterogeneity, level 2: within-study heterogeneity); β was estimated based on multiplying B by the SD of creativity and diving by the SD of effect size on the outcome; removed as influential studies: 1 85 , 86 ; 2 85 ; 3 87 ; 4 10 ; 5 88 ; 6 89 ; 7 90 ; 8 91 ; 9 92 , 93 ; 10 94 .
Figure 3 Estimate of the association between effect size and creativity rating of the physical activity interventions.
…”
Section: Resultsmentioning
confidence: 99%
“… Significant associations are highlighted in bold; k = number of studies; I 2 at study level (level 3: between-study heterogeneity, level 2: within-study heterogeneity); β was estimated based on multiplying B by the SD of creativity and diving by the SD of effect size on the outcome; removed as influential studies: 1 85 , 86 ; 2 85 ; 3 87 ; 4 10 ; 5 88 ; 6 89 ; 7 90 ; 8 91 ; 9 92 , 93 ; 10 94 . …”
Section: Resultsmentioning
confidence: 99%
“…Further, it is also noteworthy, in the context of an integrated view, that the beneficial effects of the QMT are not only restricted to motor functions or “cool” executive functions. Across different studies, QMT has been strongly linked to internally oriented attention, increased mindfulness, and altered states of consciousness as well as to increased creativity among healthy school-aged children [ 244 , 260 ], demonstrating its capabilities in improving affective processes and emotional well-being [ 243 ]. Finally, while improving reading and writing is, and should remain, the most important aim of any intervention in dyslexic participants, improving also well-being and self-efficacy may be crucial for the overall quality of life in participants affected by dyslexia.…”
Section: Discussionmentioning
confidence: 99%
“…In the last ten years, many studies investigated different effects of QMT on varied samples of participants. These studies demonstrated how QMT can improve the cognitive and psycho-emotional functioning of its practitioners [ 17 , 229 , 235 , 237 , 242 , 243 , 244 ]. In particular, from a cognitive perspective, QMT induced gains in ideational flexibility which likely resulted from motor and cognitive inhibition.…”
Section: Quadrato Motor Training and Dyslexiamentioning
confidence: 99%
“…Considering the importance of creativity and the fact that creativity is a trainable trait (Saavedra & Opfer, 2012), it is of societal importance that creativity is stimulated. A multitude of strategies to increase creativity have been suggested: Hatha yoga, music listening, meditation, to shift the perspective of something, to find or apply an analogy, and traveling (Bollimbala, James, & Ganguli, 2020; Frith & Loprinzi, 2018; Marson et al, 2021; Runco, 2014). Another intervention suggested to increase creativity that has received increasing attention is physical activity (PA).…”
mentioning
confidence: 99%